Pengukuran Kesiapan Pemerintah Kabupaten Minahasa dalam Menerapkan Smart Regency - Elisa Eunike Lumintang; Arie S.M. Lumenta; Stanley D.S. Karouw (Universitas Sam Ratulangi, 2021)
Abstract — The Minahasa Regency Government is in the stage of implementing Smart City or Smart Regency in helping to solve city problems and helping the Minahasa Regency Government to improve public services. This study aims to measure the readiness score of the Minahasa Regency Government in the application of smart regency or smart city. The method used in this study is to use the SE Readiness Research Model for Smart City Users in the Regency / City which is based on the theories of the previous framework (Framework Technology-Organization-Environment (TOE), Rural Technology Acceptance Model (ruTAM), Molla - Licker ) which consists of the variables Demographic Factors, Facilitating Conditions, Security Concern, Perceived Usefulness, Perceived Ease of Use, Behavioral Intention of Use, Top Management Support, Government, Organizational Readiness. The measurement results show that the parameters mentioned above are Facilitating Conditions with the final measurement results (score: 0.76), Security Concern (score: 0.8), Perceived Usefulness (score: 0.79), Perceived Ease of Use (score: 0.75), Behavioral Intention of Use (score : 0.75), Top Management Support (score : 0.76), Government (score : 0.77), Organizational Readiness (score : 0.69). The measurement results show that the Minahasa Regency Government is ready to implement smart regency. Keywords - Minahasa District Government; Readiness Measurement; Smart Regency; SE readiness. Abstrak — Pemerintah Kabupaten Minahasa dalam tahapan menuju penerepan Smart City atau Kabupaten Cerdas dalam membantu penyelesaian permasalah kota dan membantu Pemerintah Kabupaten Minahasa meningkatkan peleyanan publik. Penelitian ini bertujuan untuk mengukur skor kesiapan dari Pemerintah Kabupaten Minahasa dalam penerapan smart regency atau smart city. Metode yang digunakan dalam penelitian ini yaitu dengan menggunkan Model Riset Kesiapan SE Pengguna Kota Cerdas di Kabupaten / Kota yang berdasarkan teori-teori kerangka kerja terdahulu (Framework Technology-Oragnisation-Environment (TOE), Rural Technology Acceptance Model (ruTAM), Molla - Licker) yang terdiri dari variabel Demographic Factors, Facilitating Conditions, Security Concern, Perceived Usefulness, Perceived Ease of Use, Behavioral Intention of Use, Top Management Support, Government, Organisational Readiness. Hasil pengukuran menunjukkan untuk parameter tersebut diatas adalah Facilitating Conditions dengan hasil pengukuran akhir (skor : 0.76), Security Concern (skor : 0.8), Perceived Usefulness (skor : 0.79), Perceived Ease of Use (skor : 0.75), Behavioral Intention of Use (skor : 0.75), Top Management Support (skor : 0.76), Government (skor : 0.77), Organisational Readiness (skor : 0.69). Hasil pengukuran menunjukkan bahwa Pemerintah Kabupaten Minahasa telah siap menerapkan smart regency. Kata kunci – Pemerintah Kabupaten Minahasa; Pengukuran Kesiapan; Smart Regency; Kesiapan SE.